2022
DOI: 10.1093/ecco-jcc/jjac023
|View full text |Cite
|
Sign up to set email alerts
|

What Can IBD Specialists Learn from IL-23 Trials in Dermatology?

Abstract: Background and Aims The advent of biologic drugs revolutionised the treatment of many chronic inflammatory diseases in rheumatology, dermatology, and gastroenterology. The introduction of different targeted agents closely followed the increase in knowledge of pathogenic mechanisms. The identification of IL-23 as a master regulator of ‘pathogenic’ inflammation and the consequent efficacy of IL-23 blocking agents were first proofed in psoriasis and then in other inflammatory diseases such as ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Compared with the reSURFACE 1 and 2 clinical trials, the characteristics of our patients were similar, aside from having a lower baseline PASI score, which is due to the stricter inclusion criteria of the phase 3 clinical trials. 16,24 The findings regarding the effectiveness of tildrakizumab generally confirmed those of the reSURFACE 1 and 2 trials, with better PASI 100 responses. In the reSURFACE 1 and 2 trials, tildrakizumab was found to be superior to placebo in achieving PASI75 at Week 12 (reSURFACE 1 64% vs. 6%; reSURFACE 2 61% vs. 6%).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Compared with the reSURFACE 1 and 2 clinical trials, the characteristics of our patients were similar, aside from having a lower baseline PASI score, which is due to the stricter inclusion criteria of the phase 3 clinical trials. 16,24 The findings regarding the effectiveness of tildrakizumab generally confirmed those of the reSURFACE 1 and 2 trials, with better PASI 100 responses. In the reSURFACE 1 and 2 trials, tildrakizumab was found to be superior to placebo in achieving PASI75 at Week 12 (reSURFACE 1 64% vs. 6%; reSURFACE 2 61% vs. 6%).…”
Section: Discussionsupporting
confidence: 58%
“…The retrospective study reported here is the largest real‐life study conducted to date, with a study population of 237 patients with moderate‐to‐severe chronic plaque psoriasis cared for at ten different Italian hospitals. Compared with the reSURFACE 1 and 2 clinical trials, the characteristics of our patients were similar, aside from having a lower baseline PASI score, which is due to the stricter inclusion criteria of the phase 3 clinical trials 16,24 …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In particular, three selective antagonists of the p19 subunit of IL‐23 have been developed (guselkumab, risankizumab and tildrakizumab) 8 . Guselkumab is the first human IgG1λ monoclonal antibody that inhibits IL‐23 selectively 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In particular, three selective antagonists of the p19 subunit of IL-23 have been developed (guselkumab, risankizumab and tildrakizumab). 8 Guselkumab is the first human IgG1λ monoclonal antibody that inhibits IL-23 selectively. 9 The efficacy and safety of guselkumab have been evaluated in three phase-3 clinical trials (VOYAGE1, VOYAGE2 and NAVIGATE), showing superior efficacy compared with both placebo and adalimumab.…”
Section: Introductionmentioning
confidence: 99%